The Effect of Applying Lamtoro Leaf POC on the Growth and Productivity of Odot Grass - Abdul Dalin; Julia Marissa; Adhona Bhajana Wijaya Negara (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Pennisetum purpureum is a species belonging to the elephant grass group that is commonly cultivated as forage for the main feed of ruminant livestock. One cultivar of this species is Pennisetum purpureum cv. Mott, also known as odot grass, which has more compact characteristics, allowing it to be cultivated on limited land. This study aimed to determine the effect of growth response and productivity of odot grass to the application of liquid organic fertilizer (LOF) made from lamtoro leaves as an effort to optimize ruminant feed. The study used a non-factorial Completely Randomized Design (CRD) consisting of four treatments and five replications. The results showed that the treatment with the addition of 1.5% lamtoro leaf LOF (15 ml per 1 liter of water) produced the best results in terms of growth (plant height and leaf length) and productivity (number of tillers and fresh forage yield) of odot grass (Pennisetum purpureum cv. Mott). This study concludes that the addition of lamtoro leaf LOF at a dose of 1.5% can provide more optimal results for the growth and productivity of odot grass (Pennisetum purpureum cv. Mott).